Differential involvement of the three nuclear estrogen receptors during oogenesis in European sea bass (Dicentrarchus labrax) - Zapater, Cinta (2020)
Estrogens are involved in a wide range of processes in vertebrate reproduction through ligand activation of their specific cognate receptors. In most teleosts, three nuclear estrogen receptor subtypes have been identified (Esr1, Esr2a, and Esr2b). Differences in ligand binding affinity and seasonal expression patterns in reproductive tissues among these Esr subtypes suggest distinct roles during oogenesis, vitellogenesis, and spermatogenesis. This study focuses on the role of the Esr subtypes in European sea bass (Dicentrarchus labrax) oogenesis and their endocrine regulation. The coding genes of the three Esr subtypes are highly expressed in reproduction-related tissues such as pituitary, gonad, and liver. Quantification of esr1, esr2a, and esr2b expression in the ovary and liver during a whole reproductive cycle showed different patterns depending on stage and subtype, suggesting differential roles of the three receptors in the regulation of oogenesis and vitellogenesis. Esr2a and Esr2b also showed differences in transcriptional activity and ligand affinity when functionally characterized in HEK293 cells. Finally, for the first time in teleosts, the localization of the three Esr subtypes in ovarian follicles and their regulation by gonadotropins is described. Immunodetection of the receptors revealed different distribution patterns in follicular cells and various subcellular locations of the oocyte. Gonadotropin stimulation of ovarian follicles in different stages of vitellogenesis showed a consistent induction of esrb2b expression by Fsh. All together, these data reinforce the hypothesis that each estrogen receptor plays a specific role in oogenesis.